Strengthening Spiritual Representation Through Charles Sanders Peirce's Semiotic Analysis In The Song Gala Bunga Matahari - Rahma Fatiya; Dewi Kusumaningsih; Muhlis Fajar Wicaksana; Sri Wahono Saptomo; Hanisah Hanafi (UIN Salatiga, 2025)
Spiritual representation can be found in indie song lyrics. This study aims to describe the spiritual representation in the song Gala Bunga Matahari and the relationship of the song lyrics to the listener's emotions. The method used is descriptive qualitative. The data taken are in the form of words, phrases, and sentences that have spiritual representation meaning. The data source is the lyrics of the song Gala Bunga Matahari. The data collection technique uses listening and note-taking techniques to collect the questionnaire results. The data analysis technique uses Charles Sanders Pierce's semiotic framework by identifying data using Charles' trichotomy identification format, focusing on icons, indexes, and symbols. This study's results prove that the song Gala Bunga Matahari lyrics have a spiritual representation meaning through semiotic analysis in the icon aspect. There are 3 data: the index aspect 7 data and the symbol aspect 5 data. The study also provides an overview of spiritual representation in the form of life after death through song lyrics that create an emotional connection in the listener. Therefore, this study shows that spiritual representation in the song lyrics exists and is very strong, affecting the listener's emotions. The results of this study will also increase insight for other writers and the public through scientific publications, and songs can be a means or container that poets can use to express ideas or experiences to get their place in society.